Growth factor-like activity of gliadin, an alimentary protein: implications for coeliac disease. Issue 4 (4th August 2006) - Barone, Maria V; Gimigliano, Anna; Castoria, Gabriella; Paolella, Giovanni; Maurano, Francesco; Paparo, Franco; Maglio, Maria; Mineo, Alba; Miele, Erasmo; Nanayakkara, Merlin; Troncone, Riccardo; Auricchio, Salvatore
Abstract : Background: Gliadins, a family of wheat proteins, are central to the pathogenesis of celiac disease (CD). In addition to 'immunogenic' effects, gliadin directly affects cultured cells and intestine preparations, and produces damage in vivo, via a separate 'toxic' peptide, such as A-gliadin p31–43 (P31–43). Aims: Understanding the molecular mechanisms underlying direct non T-cell mediated effects of gliadin peptides, and assessing their potential role in promoting CD. Method: Gliadin effects were tested on a number of cell lines and on cultured mucosa samples by evaluating cytoskeleton rearrangements, endocytosis, proliferation and apoptosis. Standard biochemical methods were used to assess prolonged epidermal growth factor receptor (EGFR) activation. Results: Crude gliadin peptic-tryptic peptides (PTG], or P31–43 alone, fully reproduce the effects of epidermal growth factor (EGF] on actin cytosketon, cell cycle and cell proliferation of various cell lines. Inhibitor studies demonstrate the role of EGFR in the early response to gliadin exposure, pointing to activation of the EGFR pathway. Peptide P31–43 is not similar to any EGFR ligand, but can delay inactivation of the EGFR interfering with its endocytosis. Gliadin-induced delay of EGFR endocytosis in cultured intestinal biopsies, together with S-phase entry of epithelial intestinal cells, confirm a role for EGFR activation in CD. Conclusion: The ability of gliadin peptides to delay EGFR inactivation through interference with the endocytic pathway suggests a model where gliadin fragments amplify the effects of trace amounts of EGF, and possibly of other growth factors, by prolonging receptor activation. The results, using cultures of coeliac intestinal biopsies, highlight the role of the EGF pathway in establishing and maintaining the typical atrophic and proliferative alterations of the small intestine in CD.